Emerging Space Markets - Tkatchova, Stella (Space Technology Library ;, 2018)
This book analyzes the commercial space activities and commercialization processes of the last fifteen years and maps the future challenges that NewSpace companies will face developing commercial space markets. What is new and what has happened in these markets up till now? Is there a business case for private companies for commercial space? What are the targeted commercial space markets? Who are the future customers for commercial space transportation markets? How can NewSpace companies attract investors? Can we learn lessons from traditional space industries or other companies in other areas? In what way have the last fifteen years made a difference in the evolution of space markets? Is there a future for in-situ resource mining, space debris services, in-orbit satellite servicing and sub-orbital transportation? What are the lessons learned from ISS commercialization? In addition the reader will find a synopsis of several space transportation programs, commercial space markets, future Moon and Mars missions, in-situ resource exploitation concepts, space debris mitigation projects and sub-orbital commercial markets. Major lessons learned are identified, related to the attraction of first time customers and long term R&D funding, managing technological and market risks and developing new markets and applications.